PENGARUH JUMLAH PENDUDUK TERHADAP BELANJA MODAL MELALUI PAD, DAU, DAN DAK SEBAGAI VARIABEL INTERVENING - Pertamaya Sari; Nurul Hutami Ningsih (AKUNTABILITAS, 2018)
This research is aimed at finding out the influence of total population toward capital expenditure trough local revenues, general allocation fund as an intervening variable in Regencies/Towns in South-Sumatera Provinces. This research used secondary data, obtained from Central Bureau of Statistics and Directorate General of Financial Considerations, 2014-2016. The population of this research was 11 regencies/town in South-Sumatera Province. The techniqnue of analyzing the data was through descriptive statistics, simple liner regression, hypothesis test (Ttest), determination analysis and correlation as well as path analysis and sobel test. The result showed that total population had positive significant influence toward capital expenditure, and had no significant influence toward fund alloction through local revenues as an intervening variable. In practice, total population had negative,not significant influence toward general fund allocation, and total population had positive influence of capital expenditure toward specific fund allocation as an intervening variable.